ANTESEDEN KUALITAS LAPORAN KEUANGAN LEMBAGA PERKREDITAN DESA - Sri Ayu Permatasari; I Gusti Bagus Agung Hendrawan Putra; Ni Kadek Risna; Saitri, Putu Wenny (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
Financial reports are one of the factors that influence the progress of a financial institution because accurate funding reports will result in high-quality financial statements. The better the financial reports produced, the higher the chances of making the right decisions. This research examines the impact of internal control systems, accounting knowledge, accounting information systems, the role of the supervisory board, and the use of information technology on the quality of financial reports at LPDs in Klungkung Regency. The study uses employees as samples, with 69 LPD employees selected through purposive sampling. The data in this study are analyzed using multiple linear regression. The results show that internal control systems, accounting information systems, and the use of information technology have a positive impact on the quality of financial reports. On the other hand, accounting knowledge and the role of the supervisory board do not have an impact on the quality of financial reports. Future research could expand this study by incorporating other variables that theoretically influence the quality of financial reports.